Karakteristik Komite Audit dan CSR Disclosure di Infrastructure- Konstruksi Non BUMN - Gede Andhika Widdharma Putra; Rousilita Suhendah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research empirically tests the influence of audit committee characteristics, namely audit committee independence, audit committee size, expertise, audit committee finances, audit committee meeting frequency, audit committee gender differences on the quality/extent of corporate social responsibility disclosure for the 2018-2022 period. The dependent variable used in this research is the extent of corporate social responsibility disclosure. This research uses quantitative research methods with secondary data obtained from annual reports of non-BUMN infrastructure and construction industry companies listed on the IDX. There are 150 data from 30 companies selected as research samples based on the purposive sampling method. Data processing in this study was tested using Eviews 12 Student Version Lite. The results of this research show that the independence of the audit committee, the financial expertise of the audit committee and the frequency of audit committee meetings have a significant positive effect on the extent of CSR disclosure. Meanwhile, audit committee size and audit committee gender differences have no influence on the extent of CSR disclosure.